Anticancer Activity of Opuntia Cochenillifera Extract Against Triple-Negative Breast Cancer Cells via Apoptosis Induction and Bioinformatics-Based Target Prediction - Alaydrus, Ali Akbar; Alaydrus, Hasan Shodiq; Assegaf, Adilah (Scripta Medica, 2026)
Background/Aim: Breast cancer remains one of the most commonly diagnosed cancers among women worldwide and is a significant public health concern. Aim of this study was to investigate the in vitro anticancer activity of Opuntia cochenillifera ethanolic extract (EOC) against triple‑negative breast cancer (TNBC) cells and to predict potential molecular targets involved in its mechanism of action through bioinformatics analysis. Methods: Fresh O cochenillifera leaves were extracted by ethanol maceration. Phytochemical constituents were analysed using qualitative screening, thin‑layer chromatography (TLC), UV–Vis spectrophotometry and Fourier transform infrared (FTIR) spectroscopy. Cytotoxicity against MDA‑MB‑231 TNBC cells was determined via MTT assay and morphological assessment. Apoptosis induction was quantified by Annexin V–FITC/PI flow cytometry. Potential molecular targets were identified through integrated bioinformatics platforms, including STITCH, SEA, SwissTargetPrediction, STRING and Cytoscape, followed by pathway enrichment analysis. Results: Phytochemical analysis revealed the presence of alkaloids, flavonoids, phenolics, saponins and steroids, with flavonoids as predominant constituents (68 mg/g extract). FTIR spectra confirmed hydroxyl, aliphatic, aromatic and carbonyl functional groups consistent with phenolic and flavonoid structures. EOC exhibited dose‑dependent cytotoxicity against MDA‑MB‑231 cells, with an IC₅₀ of 270.63 µg/mL, accompanied by morphological and flow‑cytometric evidence of apoptosis. Network pharmacology analysis identified 34 apoptosis‑related target genes, including six hub genes (CDKN1A/p21, TP53, MAPK1, MAPK3, AKT1 and FOXO3), associated with TP53‑p21 signalling, MAPK cascades and mitochondrial stress‑induced apoptosis pathways. Conclusion: O cochenillifera ethanolic extract demonstrated significant cytotoxic and pro‑apoptotic effects in TNBC cells, potentially mediated through TP53‑p21 and MAPK pathway modulation. These findings suggest that O cochenillifera is a promising candidate for further investigation as a natural adjuvant therapeutic agent for triple‑negative breast cancer.